Causes of mountain meadow soil chemical degradation in long-term fertiliser experiment - M. Kopeć (Plant, Soil and Environment, 2002)
The fertilising experiment was set up in 1968 on the mountain meadow (720 m a.s.l.) in Czarny Potok near Krynica (20°8' E, 49°4' N). The experiment was conducted on the acid Cambi soil and comprised objects fertilised with two nitrogen forms and two doses against the background of PK fertilisation, the untreated object, and plots with unilateral P and N fertilisation. The paper concerns 30 years of investigations (1968-1997) of the effect of different NPK fertilisation on the dynamic of yields and the meadow sward quality against a background of the same treatments. The dynamic of the botanical composition was presented as well as the dynamic of the grassland yield potential with systematic mineral fertilisation and liming. The application of nitrogen fertilisation with the rate of 90 N.ha-1 + PK under mountain conditions and systematic liming of the meadow enables to maintain or increase production over the long period, to decrease the production risk and to prevent degradation of the environment and natural resources.